A clitoral verrucous carcinoma in an area of lichen planus has aggressive features. Issue 1 (December 2017) - Tjalma, Wiebren; Siozopoulou, Vasiliki; Huizing, Manon
Abstract Background Verrucous carcinoma of the vulva is extremely rare. It is a slow growing, low malignant variant of a squamous cell carcinoma with a cauliflower appearance. Women with lichen planus have an increased risk of developing vulval cancer. Case presentation A 79-year-old woman consulted for vulval itching. On clinical examination, a 3-cm large verrucous clitoral cancer in an area of lichen planus was seen. Based on her last clinical examination, the growth was estimated to be 1 cm2 per month with an invasion depth after 6 months of 5 mm. A tumor developing in an area of lichen planus appears to have more aggressive features. This is the first time that the growth of a verrucous carcinoma has been documented in an area of lichen planus. Conclusions Clinicians and patients should be aware of the aggressive behavior of cancers developing in areas of lichen planus and adjust their surgical management together with the follow-up strategy.